Revolutionary nostalgia : retromania, neo-burlesque and consumer culture - Cervellon, Marie-Cécile; Brown, Stephen, 1955 March 23- (Emerald Publishing Limited, 2018)
Nostalgia, they say, is not what it used to be. Once a witticism, this statement about the past has come to pass. Nostalgia really isn't what it used to be. Less than a generation ago, it was regarded as reactionary, as regressive, as reprehensible. Now, it is considered conducive to health, wealth, and human wellbeing. It is something that helps sell products and move merchandise, an underexploited critical resource with emancipatory potential.Nowhere is this transformation better illustrated than in the neo-burlesque community, whose members not only embrace the art-form's golden age, and happily acquire heritage goods and vintage services, but turn their nostalgic leanings to emancipatory effect. They are retro revolutionaries, feather boa-wearing insurgents who find women's liberation in sequins and stilettos.This book shines a spotlight on weapons-grade nostalgia, indicating how it is integral to insurrections throughout history, be they political, technological, or cultural. It reveals, through a combination of empirical ethnographic research and revolutionary literary criticism, the part nostalgia plays in a subversive consumer collective that uses fans, fishnets, and frivolity to fight for the right to party against patriarchy and find a fourth-wave form of female emancipation that foregoes old-school feminist fault-finding for good old-fashioned fun, fun, fun.
Keywords: Nostalgia -- Social aspects.; Retromarketing.; Consumer behavior.; Postmodernism.; Social Science -- Popular Culture.; Society & culture: general.; elektronické knihy; electronic books